Tarrazú y Orosí: Cambios en la cadena de comercialización del café y estrategias ante la liberalización del mercado, 1989-2006 - Sandí Morales, José Aurelio; Zúñiga Rivera, Carolina; Montero Mora, Andrea (Revista de historia., 2007)
This article focuses on the changes the Orosi and Tarrazú coffee marketing system had to deal with after the markets liberalization, and the strategies implemented by the processors and exporters of the coffee bean in order to tackle the critical situations that arose from the rupture of the International Coffee Agreement. This paper addresses the object of the free market and its impact on the domestic coffee-producing system, the dynamics of the coffee-processing and export structures in each region under study, and the key players response to the market crisis.